POTRET KEHIDUPAN WARIA DI KOTA PEKANBARU (STUDI KASUS WARIA DI PANAM JALAN SOEBRANTAS KOTA PEKANBARU) - Solikhah, Nurul; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted on transvestites at Panam Jalan Soebrantas Kota Pekanbaru. The purpose of this study is to analyze the driving factors into transvestites at Panam Jalan Soebrantas Kota Pekanbaru. The focus of this study is to analyze the profile of transsexual life at Panam Jalan Soebrantas Kota Pekanbaru.  Sampling technique in this study is snowball sampling and set the number of samples as many as 6 people. The author uses qualitative methods and Instruments data is observation, interview and documentation guide. According to research that has been done can be concluded that the profile of transvestites, among others, the average age of twenty years to fifty years. The subject of this study can be said to have deviant behavior to become a transvestite that occurs among adolescents and adult age, some of them become transsexuals because experiencing same-sex sexual traumatic and there is also a congenital from a small and then experience same-sex sexual relations on the basis of likes like. After doing research it is known that the average of transvestites have a good level of education, even one of the respondents is an activist movers of transvestites, and there are some transvestites who have achievements such as following the congregation when still in high school and after graduating high school. even among those who have attended college even though only two semesters. One of the six respondents is the original residents of Pekanbaru the rest comes from different places and not the natives but the migrants. In terms of transgender work is very tends to work disalon and as a prostitute, singer, and private employees. From the various profei they earn an average of three million rupiah to ten million rupiah per month. In the religious side of the average transvestites are Muslim, only one of them is Christian. They are transvestites who are still obedient to certain religious teachings have confidence.   Keywords: Transvestite, Transsexual